El coaching como herramienta de éxito en las organizaciones (2020)
The work presented below is developed in the description and foundation of coaching, as a key inventive that generates the acquisition and development of habits in whose individuals they carry out and put into practice, this will allow to create an environment in which the permanence of the status quo. This development allows to show how to apply coaching from the different perspectives and forms that exist, emphasizing mainly on the mechanics and methodology of how it can help the development of a company, optimizing not only productivity, but also the spinal column that are their workers and Managers. In order to carry out a complete work that covers a large percentage of the perspectives generated by coaching, the development of a theoretical framework will be carried out in which the different aspects ranging from the parts that make the development of this methodology possible can be found, also going through the different steps that have to be done in a correct and completely effective way of coaching Within training you can develop habits, promote the growth of the people involved in this technique, this type of growth from individual development to group development within an organization. This type of techniques promotes the development of competencies, leadership and continuous improvement, generating an optimization of the processes in which they want to improve.